Developing an Interventional Radiology Service - Nguyen, Luan D. (Digestive Disease Interventions, 2024)
Interventional radiology (IR) is a rapidly developing field among medical activities. This review summarizes the history of IR since the inception of angiography, the present situation regarding IR's position in the clinical setting, and proposal of standardized education and further cooperation in the field. This review also focuses on sharing the author's experience in establishing an extensive IR service line, and how this will become the standard model for the Vietnamese Society of Interventional Radiology.
Keywords: interventional radiology; digital subtraction angiography; specialty